ENHANCING ENGLISH COMMUNICATION SKILL AMONG THE LEARNERS AT THE HIGHER SECONDARY LEVEL - et al., A. PUNITHA (International Journal of Control and Automation, 2019)
Like in India people have to learn English language apart from Hindi for their professional growth. Courses like medical, engineering and other professional courses are being taught in English language, and the books are also published in English language. The significance of English is not limited to the education of an individual. But it is a beginning language of international business and corporate sector across the globe. Students at the higher secondary level of India wherever seek their career either in India or abroad, they are expected to have good command over English language. Undoubtedly it can be said that a student whether willing to become a part of government sector or corporate sector, he/she will have to learn English language and to open the doors for making their career bright.